2018
DOI: 10.1159/000490919
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Monitoring of Patient Mobility for 18 Months Using Inertial Sensors following Traumatic Knee Injury: A Case Study

Abstract: Continuous patient activity monitoring during rehabilitation, enabled by digital technologies, will allow the objective capture of real-world mobility and aligning treatment to each individual’s recovery trajectory in real time. To explore the feasibility and added value of such approaches, we present a case study of a 36-year-old male participant monitored continuously for activity levels and gait parameters using a waist-worn inertial sensor following a tibial plateau fracture on the right side, sustained as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Previous work has shown effective gait speed monitoring in healthy populations by algorithms combining individual detection and parameterization of steps with estimation of gait speed for a given step. Step detection has been achieved with a range of methods including continuous wavelet transform [16,22], whereas gait speed estimation is typically done by using supervised methods such as support vector regression [3]. However, when applied to slow-walking populations, for example, multiple sclerosis (MS), these algorithms produce an observable overestimation of gait speed, particularly in the slowest walkers [6], presumably because of varying relevance of the feature set in patients with pathological gait relative to training sets.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work has shown effective gait speed monitoring in healthy populations by algorithms combining individual detection and parameterization of steps with estimation of gait speed for a given step. Step detection has been achieved with a range of methods including continuous wavelet transform [16,22], whereas gait speed estimation is typically done by using supervised methods such as support vector regression [3]. However, when applied to slow-walking populations, for example, multiple sclerosis (MS), these algorithms produce an observable overestimation of gait speed, particularly in the slowest walkers [6], presumably because of varying relevance of the feature set in patients with pathological gait relative to training sets.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that patient compliance patterns were highly variable, with some patients greatly exceeding the requested wear time and others contributing far less. As previously reported [16], we sought to define a set of minimum thresholds for compliant wear time from which gait behaviors could be stably estimated. This 2-component threshold (hours per day and days around visits) is an attempt to maximize the number of patients included in the analysis and minimize variation because of the sampling of an unrepresentative, too short period of a patient’s daily life.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to gait speed, for which there are few published studies, step detection is well studied with multiple devices on multiple populations [2126], however different validation protocols, populations and test scenarios make a comparison between existing results challenging, and there is no consensus about standardized setting [21,27,28]. Khan et al and Lipperts et al tested and validated their algorithms in an elderly population[27,28].…”
Section: Discussionmentioning
confidence: 99%